Da guerra à união: uma abordagem histórica da caminhada da Associação Evangélica de Comunidades e do Sínodo Evangélico-Luterano até a sua fusão e formação do Sínodo Evangélico-Luterano Unido - Baade, Joel Haroldo (2007)
This master s thesis is an analysis dealing with confessional identity and ethnic discourse in the context of the approximation of two synods which would constitute the IECLB in 1949, these being, the Associação Evangélica de Comunidades (Evangelical Association of Congregations) and the Sínodo Evangélico Luterano (Evangelical Lutheran Synod), pointing out the conflicts in the process of intersynodical convergence at the institutional and congregational levels. This thesis is divided into three chapters. In the first chapter the confessional issues involved in the relation between the two synods is discussed. The central part of this chapter is the reproduction of the discussions of the educational institutions on the part of the pastors and the divergence of this discussion in relationship to the congregational emphases. In the second chapter we describe the importance of ethnic thinking that occurred in the synods, its relation to the German and Brazilian political situation and to what extent this marked the intersynodical relations. In the third chapter we discuss the coming together and merger of the synods and in what way this process was influenced by the confessional and ethnic discussions. In general, one can say that the coming together of the Associação Evangélica de Comunidades and the Sínodo Evangélico Luterano is marked by conflicts, differences of opinion and wars , but also clear signs of Christian commitment and the search for cooperation and unity are evident.